Welcome - Lioret, Philippe; Courcol, Emmanuel (Cameo media, 2010)
Bilal is 17 years old, a Kurdish boy from Iraq. He sets off on an adventure-filled journey across Europe. He wants to get to England to see his love who lives there. Bilal finally reaches ...